Automatic, computer-based speech assessment on edentulous patients with and without complete dentures - preliminary results - Stelzle, Florian; Ugrinovic, Biljana; Knipfer, Christian; Bocklet, Tobias; Nöth, Elmar; Schuster, Maria; Eitner, Stefan; Seiss, Martin; Nkenke, Emeka (Journal of Oral Rehabilitation, 2010)
Dental rehabilitation of edentulous patients with complete dentures includes not only aesthetics and mastication of food, but also speech quality. It was the aim of this study to introduce and validate a computer-based speech recognition system (ASR) for automatic speech assessment in edentulous patients after dental rehabilitation with complete dentures. To examine the impact of dentures on speech production, the speech outcome of edentulous patients with and without complete dentures was compared. Twenty-eight patients reading a standardized text were recorded twice - with and without their complete dentures in situ. A control group of 40 healthy subjects with natural dentition was recorded under the same conditions. Speech quality was evaluated by means of a polyphone-based ASR according to the percentage of the word accuracy (WA). Speech acceptability assessment by expert listeners and the automatic rating of the WA by the ASR showed a high correlation (corr = 0.71). Word accuracy was significantly reduced in edentulous speakers (55.42 +/- 13.1) compared to the control group's WA (69.79 +/- 10.6). On the other hand, wearing complete dentures significantly increased the WA of the edentulous patients (60.00 +/- 15.6). Speech production quality is significantly reduced after complete loss of teeth. Reconstitution of speech production quality is an important part of dental rehabilitation and can be improved for edentulous patients by means of complete dentures. The ASR has proven to be a useful and easily applicable tool for automatic speech assessment in a standardized way.
Keywords: speech quality; automatic speech recognition; objective speech assessment; edentulism; complete dentures; oral rehabilitation